EU-China agricultural trade in relation to China`s WTO accession - Xing, Liu; Huan-Niemi, Ellen (MTT, 2002)
EU agricultural trade with China has remained deficit since 1990. The unsteady exports were responsible for the deficit. Oilseeds, oilseed oils, cereals, dairy products, and meat products are the staple products that the EU have exported to China in 1990s. EU export of oilseeds jumped to the first position in 1999 because EU exports of vegetable oils (mostly oilseed oils) have declined gradually since the middle of the 1990s. The cause is China's policy shift towards domestic crushing of oilseeds with the aim of retaining the value-added activity in China. As a result, China is able to produce more value-added vegetable oils at the expense of the decrease in the imports of oilseed oils. In the cereals sector, EU export of wheat products in value shrank over 99% in 1999 compared to 1995 due to harsh competition and slowing demand in the Chinese market. Meanwhile, EU export of barley has performed increasingly well in China's market due to the growing demand for brewing and decreasing domestic production in China. EU agricultural imports have been steadily growing throughout the period. Labour-intensive products have become the dominant products that the EU imported from China due to the cheap labour cost in China. Netherlands, France, and Germany are the three major players in the agricultural trade with China. Under the framework of the WTO, China has committed to make vast reforms on its agricultural trade policy. China agreed to improve market access, eliminate non-tariff barriers, and also not to maintain or introduce any export subsidies on agricultural products. The impact of these reforms on EU agricultural trade with China will be significant, affecting mostly EU agricultural exports to China. Barley and rapeseed oil are likely to benefit the most from the reduction in tariff. Considerable tariff cuts will also further lower the price of EU dairy products and meat products in the Chinese market. Freer trade for oilseeds and oilseed oils will further stimulate China's domestic demand for imports. Consequently, EU exports of rapeseed and rapeseed oil are expected to grow strongly in the next few years. The increasing participation of private companies into Chinese agricultural trade will increase EU opportunities to export more of these products. The reason is that China will not be able to use state trading enterprises (STEs) as a policy instrument to limit imports in order to support domestic production. These findings imply that changes in China's agricultural policy as a member of the WTO will have a favourable impact on EU agricultural exports to China in the next few years. Furthermore, EU's export of barley, rapeseeds and rapeseed oil will expand more rapidly compared to the other agricultural products.
Keywords: Ma; EU; WTO; markkinoillepääsy; Euroopan unioni; Kiina; maataloustuotekauppa; tullit; EU; China; WTO; agricultural exports; market access; non-tariff barriers